Diversidade populacional, vias de transmissão e virulência de Streptococcus agalactiae isolados de tilápias do Nilo (Oreochromis niloticus) - Mian, Gláucia Frasnelli (2009)
Streptococcus agalactiae is an emerging pathogen in Nile tilapia. To investigate aspects of the epidemiology, transmission, virulence and the genetic diversity of S. agalactiae infections, nine outbreaks of meningoencephalitis and septicemia in Nile tilapia farms in Brazil were analyzed. The 16S rRNA gene and ISR were utilized with molecular marker of the genetic variability. Records from the outbreaks revealed large variation in the weight of fish affected, high mortality, and disease occurrence at water temperatures above 27°C. S. agalactiae was isolated from diseased fish from all farms, and 29 strains were identified by phenotypic tests and 16S rRNA gene sequencing. All strains were highly virulent; for example, strain SA20-06 had an LD50 of 6.14´101.17 CFU. Considerable variation in biochemical profile was observed and 13 different phenotypic variants were finding. To investigate S. agalactiae transmission, we conducted cohabitation assays with diseased and healthy fish and fish challenges using an immersion bath or branchial inoculation. The disease was reproduced with characteristic clinical signs and S. agalactiae was reisolated in all trials. The phylogenetic analyzes showed five different profiles for the sequences of 16S rRNA gene, presenting significant variability to the 29 strains of S. agalactiae evaluated. Different genetic patterns were observed in distinct isolates of the same farm. This variability was not compatible with the phenotypic variety described here, as well as with virulence of the strains of the S. agalactiae. The ISR showed to be highly conserved among the bacterial fish isolates.